1991
DOI: 10.1007/bf00174396
|View full text |Cite
|
Sign up to set email alerts
|

Arrangement of neurons in the medullary reticular formation and raphe nuclei projecting to thoracic, lumbar and sacral segments of the spinal cord in the cat

Abstract: The distribution of neurons in the medullary reticular formation and raphe nuclei projecting to thoracic, lumbar and sacral spinal segments was studied, using the technique of retrograde transport of horseradish peroxidase (HRP), alone or in combination with nuclear yellow (NY). Retrogradely labeled cells were observed in the lateral tegmental field (FTL), paramedian reticular nucleus, magnocellular reticular nucleus (Mc), in the gigantocellular nucleus (Gc), lateral reticular nucleus (LR), lateral paragiganto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
20
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 24 publications
7
20
0
Order By: Relevance
“…Labeling has been consistently reported in these same regions. Taken together with results from previous anterograde studies (Zemlan et al, 1984;Jones and Yang, 1985;Martin et al, 1985b;Holstege and Tan, 1987;Kausz, 1991), the ventral portion of the gigantocellular and the lateral paragigantocellular nuclear complex (Gi-LPGi) appears to be a likely source of supraspinal influence over a variety of spinal reflexes.Extensive review of the inhibitory role of the Gi-LPGi on sexual function is presented elsewhere (McKenna, 2000;Steers, 2000). To briefly summarize, behavioral studies support the hypothesis that this ventral medullary reticular area exerts descending inhibitory control of sexual reflexes (Marson and McKenna, 1990;Yells et al, 1992;Liu and Sachs, 1999).…”
supporting
confidence: 62%
“…Labeling has been consistently reported in these same regions. Taken together with results from previous anterograde studies (Zemlan et al, 1984;Jones and Yang, 1985;Martin et al, 1985b;Holstege and Tan, 1987;Kausz, 1991), the ventral portion of the gigantocellular and the lateral paragigantocellular nuclear complex (Gi-LPGi) appears to be a likely source of supraspinal influence over a variety of spinal reflexes.Extensive review of the inhibitory role of the Gi-LPGi on sexual function is presented elsewhere (McKenna, 2000;Steers, 2000). To briefly summarize, behavioral studies support the hypothesis that this ventral medullary reticular area exerts descending inhibitory control of sexual reflexes (Marson and McKenna, 1990;Yells et al, 1992;Liu and Sachs, 1999).…”
supporting
confidence: 62%
“…Monosynaptic EPSPs could be mediated by ipsilaterally descending reticulospinal neurons, via crossed axon collaterals terminating in the ven-tral horn (Nyberg-Hansen, 1965;Kausz, 1991;Matsuyama et al, 1999), as indicated by connections labeled 1 and 2 in Figure 1 A. Monosynaptic EPSPs could also be evoked by contralaterally descending reticulospinal neurons (Nyberg-Hansen, 1965;Mitani et al, 1988b,c;Matsuyama et al, 1993) and their local axon collaterals ( Fig. 1 A, 3).…”
Section: Resultsmentioning
confidence: 92%
“…Allen and Cechetto (1994) used unilateral dye injections in the rat thoracic IML to label neurons in the gigantocellular and raphe nuclei in the medulla. In the cat, Kausz (1991) injected horseradish peroxidase into the IML on one side of the S2 spinal cord segment (the cat homolog to the corresponding region L6-Sl in the rat) and found labeled neurons bilaterally in the medullary reticulum homologous to those regions in the rat containing PRV-IR neurons, including GiV, GiA, and the raphe pallidus and obscurus. Taken together, these reports clearly support the current results and suggest that there is a direct connection between PRV-IR labeled neurons in the lumbosacral cord and the reticular neurons in the medulla.…”
Section: Brainmentioning
confidence: 99%